Soil physical and biological properties in an integrated crop-livestock system in the Brazilian Cerrado - Bonetti, João de Andrade; Paulino, Helder Barbosa; Souza, Edicarlos Damascena; Carneiro, Marco Aurélio Carbone; Oliveira, Jeander Caetano (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the soil physical and biological properties in an integrated crop-livestock system (ICLS), with or without cattle grazing, in different seasons. The experiment was carried out in the Cerrado biome, in Brazil, in a Rhodic Eutrudox. The treatments consisted of grazing areas (Urochloa ruziziensis) at 0.25, 0.35, and 0.45 m heights (with soybean cultivation after grazing) and of nongrazed areas. The ICLS had no negative effects on soil bulk density, total porosity, macroporosity, and microporosity. After ICLS implementation, the values of soil bulk density decreased, and those of soil macroporosity increased, in the grazed and nongrazed areas. However, after three years, bulk density and macroporosity were reestablished to values similar to those before ICLS implementation. Soil penetration resistance was higher in the ICLS, mainly at 0.00–0.05 m soil depth. After four years, ICLS promoted the increase of microbial biomass C and N and the reduction of the metabolic quotient. The microbial biomass carbon and the metabolic quotient were related to the weighted mean diameter. ICLS benefits to soil physical and biological properties are associated with adequate ICLS implementation, adequate grazing height (0.35 m), and maintenance of soil cover.